A CORRELATION STUDY: Understanding and Ability to Appreciate Proverbs in Semantics Class - Adolf Bastian (Universitas Lancang Kuning, 2015)
The purpose of this article is to investigate the correlation between students’ understanding in semanticsand their ability to appreciate English proverbs at the seventh semester of English department students in Lancang Kuning University, Pekanbaru. Based on the findings and discussion in chapter IV, the result was in line with the researcher’s hypothesis that there was significant correlation between students’ understanding in semantics and their ability to appreciate English at the Seventh Semester of English Education Department Faculty of Education and Teachers Training University of Lancang Kuning. The result of semantics test could be categorized “very good” because the percentage of the students who got very good category was 75%. Whereas, the result of English proverbs test could be categorized “very good” because of the percentage of the students who got very good category was 72%. It was found that the more increases semantics score, the more increases also English proverbs score. So, it was strong influence for variable X which was semantics to influence variable Y which was English proverbs and vice versa. The data reveals that the correlation coefficient was 0.846 which was close to +1.00, it meant that there was positive correlation between students’ understanding in semantics and their ability to appreciate English proverbs.